THE CRITICAL SUCCESS FACTORS FOR LEAN SIX SIGMA IMPLEMENTATION IN SMALL-AND-MEDIUM-SIZED ENTERPRISES - Attar, Muhammad Talal (The South African Journal of Industrial Engineering, 2023)
Lean six sigma (LSS) is an important business strategy for organisations, including small and medium-sized enterprises (SMEs). Over the years, SMEs have had a potentially significant impact on various countries’ gross domestic product (GDP). The main purpose of this research is to investigate the critical success factors (CSFs) for lean six sigma (LSS) implementation in the Kingdom of Saudi Arabia’s SMEs, and to contribute to discovering the factors that lead to business success, increase revenue, and enhanced competitive advantages. The study identified 29 factors from previous research in order to guide the successful implementation of LSS in the SME sector in Saudi Arabia in particular. The CSFs were refined, producing a consolidated list of 14 factors. A principal components analysis (PCA) identified four main factors: leadership support and management structure, technological capabilities, knowledge acquisition, and creativity and innovation. These factors could influence the success of SMEs in Saudi Arabia by adopting LSS in their business processes.